Echocardiographic Profiling Predicts Clinical Outcomes After Mitral Transcatheter Edge‐to‐Edge Repair - Taha Hatab; Sahar Samimi; Rody G. Bou Chaaya; Fatima Qamar; Chloe Kharsa; Priscilla Wessly; Nadeen Faza; Stephen H. Little; Marvin D. Atkins; Michael J. Reardon; Neal S. Kleiman; William A. Zoghbi; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Prior studies investigating the impact of residual mitral regurgitation (MR), tricuspid regurgitation (TR), and elevated predischarge transmitral mean pressure gradient (TMPG) on outcomes after mitral transcatheter edge‐to‐edge repair (TEER) have assessed each parameter in isolation. We sought to examine the prognostic value of combining predischarge MR, TR, and TMPG to study long‐term outcomes after TEER. Methods and Results We reviewed the records of 291 patients who underwent successful mitral TEER at our institution between March 2014 and June 2022. Using well‐established outcomes‐related cutoffs for predischarge MR (≥moderate), TR (≥moderate), and TMPG (≥5 mm Hg), 3 echo profiles were developed based on the number of risk factors present (optimal: 0 risk factors, mixed: 1 risk factor, poor: ≥2 risk factors). Discrimination of the profiles for predicting the primary composite end point of all‐cause mortality and heart failure hospitalization at 2 years was examined using Cox regression. Overall, mean age was 76.7±10.6 years, 43.3% were women, and 53% had primary MR. Two‐year event‐free survival was 61%. Predischarge TR≥moderate, MR≥moderate, and TMPG≥5 mm Hg were risk factors associated with the primary end point. Compared with the optimal profile, there was an incremental risk in 2‐year event‐rate with each worsening profile (optimal as reference; mixed profile: hazard ratio (HR), 2.87 [95% CI, 1.71–5.17], P<0.001; poor profile: HR, 3.76 [95% CI, 1.84–6.53], P<0.001). Echocardiographic profile was statistically associated with the 2‐year mortality end point (optimal as reference; mixed profile: HR, 3.55 [95% CI, 1.81–5.96], P<0.001; poor profile: HR, 3.39 [95% CI, 2.56–7.33], P=0.02). Conclusions The echocardiographic profile integrating predischarge TR, MR, and TMPG presents a novel prognostic stratification tool for patients undergoing mitral TEER.